HUBUNGAN PENGETAHUAN DAN SIKAP PETUGAS LABORATORIUM PATOLOGI KLINIK DALAM MENGGUNAKAN ALAT PELINDUNG DIRI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Alhayati, Dinul Fitriani; Restuastuti, Tuti; ", Fatmawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Clinical Patology laboratory officers is highly risk to infection and oocupational accident causes by exposed with reagent and and clinical speciment. Personal Protective Equipment (PPE) such as googles, gloves, protective coats, boots and masks will be needed to prevent the risk. This research conducted to determine the correlation between clinical pathology laboratory officers’ knowledges and attitudes in Personal Protective Equipment utilization in RSUD Arifin Achmad Riau Province, which has implemented on January-June 2014. This is an analytic survey study with cross-sectional method. About 34 workers have obtained as samples. Univariate and bivariate analytic processed by using Fisher test. Results of correlation between knowledges and attititudes on workers in Personal Protective Equipment utilization showed a value p>0,05, which was leading to a conclusion the association between knowledges, attitudes, and Personal Protective Equipment utilization on Clinical Pathology laboratory officer of RSUD arifin Achmad Riau Province couldn’t be found.Key words: Knowledge, attitude , Personal Protective Equipment utilization